2006
DOI: 10.1007/s11095-006-9097-z
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxyacetophenone-Induced Choleresis in Rats is Mediated by the Mrp2-Dependent Biliary Secretion of Its Glucuronide Conjugate

Abstract: These results demonstrate that the major biliary metabolite of 4-HA in rats is the 4-O-beta-glucuronide, a compound that is secreted into bile at high concentrations, and may thus account in large part for the choleretic effects of 4-HA. Transport of this metabolite across the canalicular membrane into bile requires expression of the Mrp2 transport protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Indeed, two glucuronide metabolites of THA have been identified (S. Khamdang, A. Suksamrarn, and P. Piyachaturawat, unpublished observation). This finding is consistent with an earlier report that the glucuronide conjugation of phloracetophenone is the major biliary metabolite (11,16). Mrp2, the multispecific resistance-associated protein 2, plays an important role in the biliary excretion of a number of endogenous and exogenous compounds including glucuronide, glutathione, and sulfates conjugates (7).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, two glucuronide metabolites of THA have been identified (S. Khamdang, A. Suksamrarn, and P. Piyachaturawat, unpublished observation). This finding is consistent with an earlier report that the glucuronide conjugation of phloracetophenone is the major biliary metabolite (11,16). Mrp2, the multispecific resistance-associated protein 2, plays an important role in the biliary excretion of a number of endogenous and exogenous compounds including glucuronide, glutathione, and sulfates conjugates (7).…”
Section: Discussionsupporting
confidence: 93%
“…In our earlier study on the choleretic effect of 4-monohydroxyacetophenone (a THA analog), there was a clear parallel increase in bile flow and metabolites in bile. Moreover, 4-monohydroxyacetophenone failed to exert a choleretic effect in TR Ϫ rats where the excretion of metabolites was absent (16). By analogy, the metabolites of THA should also be excreted in bile and provide the osmotic force for stimulating bile flow.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the results with other researchers, for example, 4-hydroxyacetophenone (4-HAP) is known as a bioactive compound found in several medicinal herbs, exerts a potent stimulatory effect on hepatic bile secretion [ 29 ]. This chemical inhibits the adhesion and migration of tumor cells in vitro and reduces metastatic burden in an in vivo liver metastasis model [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MRP-dependent biliary secretion pathway is also affected by other choleretically active plant compounds. Using similar approaches and experimental animals which have a congenital defect in MRP2 transporter, independent research groups demonstrated that the choleretic action of 4-hydroxyacetophenone from Aster and Artemisia species [39] and phloracetophenone from Curcuma comosa [40] is also mediated via the MRP2 secretory pathway. Results of these and other studies [41,42] suggest that the osmotic effects and excretion of the biliary electrolytes play important roles in the MRP2-dependent choleresis and may attenuate the cholestatic effects of hepatotoxins undergoing biotransformation in the liver and excretion via the MRP transporter system.…”
Section: Bsep-and Mrp-dependent Choleresismentioning
confidence: 99%